2022
DOI: 10.1371/journal.pone.0260949
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination beliefs, attitudes, and behaviours among health and social care workers in the UK: A mixed-methods study

Abstract: Background The UK began delivering its COVID-19 vaccination programme on 8 December 2020, with health and social care workers (H&SCWs) given high priority for vaccination. Despite well-documented occupational exposure risks, however, there is evidence of lower uptake among some H&SCW groups. Methods We used a mixed-methods approach—involving an online cross-sectional survey and semi-structured interviews–to gain insight into COVID-19 vaccination beliefs, attitudes, and behaviours amongst H&SCWs i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 16 publications
3
27
1
1
Order By: Relevance
“…The role of healthcare professionals in influencing the uptake of vaccination has been demonstrated in previous studies [ 45 , 46 ]. In Australia, GPs are integral in the COVID-19 response, providing primary care for patients seeking counselling about COVID-19 vaccination, with many additionally delivering COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 94%
“…The role of healthcare professionals in influencing the uptake of vaccination has been demonstrated in previous studies [ 45 , 46 ]. In Australia, GPs are integral in the COVID-19 response, providing primary care for patients seeking counselling about COVID-19 vaccination, with many additionally delivering COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 94%
“…The emphasis on 'internalised pressure' (i.e., strain) as opposed to 'reported levels of external societal pressure or demands' allowed the scale to directly capture individuals' mental health strain experience rather than their appraisal of the stressor phenomenon itself (the stressor being external societal demands/pressure). This approach deviates from a previous study [16] where 'vaccine pressure' was measured as an 'external' stressor (as opposed to a psychological strain outcome) in the form of a single-item scale capturing the level of perceived employer pressure on COVID-19 vaccinations.…”
Section: Initial Scale Development Stepsmentioning
confidence: 89%
“…Other emerging research and contemporary perspectives on mandatory COVID-19 vaccination agendas have cautioned employers against mandating or coercing employees to take the COVID-19 vaccine since this approach is more likely to exacerbate vaccine hesitancy and distrust [16,45]. In one recent study in Hong Kong which conducted a survey at two different waves (one conducted before the COVID-19 pandemic declaration and one at a later and more severe stage after the pandemic declaration), it was revealed that working individuals (especially those employed in the sales and services industries) were less willing to take the COVID-19 vaccine [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other studies noted that the death of a family member or friend due to COVID-19 increased the chance of getting vaccinated [ 28 ]. Additionally, other studies revealed that contact with people who suffered from COVID-19 [ 29 ] led to higher vaccine acceptance than employer pressure [ 30 ].…”
Section: Discussionmentioning
confidence: 99%